Effect of humanine on the Notch signaling pathway in myocardial infarction - Onat, Elif; Onalan, Ebru; Ozdem, Berna; Balgetir, Merve Kavak; Kuloglu, Tuncay (Tubitak Scientific & Technological Research Council Turkey, 2023)
Background/aim: By applying humanin (HN) before myocardial infarction (MI), its protection in myocardial injury and the possible roles of its cellular mechanism in the Notch pathway were investigated. Materials and methods: The study was carried out at Firat University Experimental Research Center (12/24/2018-12/23/2019). Spraque-Dawley rats were divided into 10 groups: I (control) (n = 6), II (HN 6 h) (n = 6), III (HN 24 h) (n = 6), IV (HN day 7) (n = 6), V (MI 6 h) (n = 7), VI (MI 24 h) (n = 7), VII (MI day 7) (n = 7), VIII (MI+HN 6 h) (n = 7), IX (MI+HN 24 h) (n = 7), and X (MI+HN day 7) (n = 7). To create MI, 200 mg/kg of isoproterenol (ISO) was administered to the rats subcutaneously. Moreover, 252 mu g/kg of HN was given intraperitoneally (ip) to the rats on its own and before MI. Molecular parameters Notch1, Notch2, Hes1, Hes2, Jagged1, Jagged2, DLL1, and DLL4 were examined using polymerase chain reaction in the heart tissue, Notch1, Hes1, and DLL4 were examined using western blot, while heart tissue was taken for histochemical examinations. Results: The mRNA expression levels of the Notch signaling members (Notch1, Notch2, Hes1, Hes2, Jagged1, Jagged2, DLL1, and DLL4) tended to decrease after MI. The Notch signaling members increased more significantly, especially toward day 7 after HN application before MI. In the western blot anylyses, the Notch1, Hes1, and DLL4 protein levels increased significantly toward day 7 in the groups given HN before MI. Moreover, the serum AST, LDH, CK-MB, and troponin I levels tended to decrease with the application of HN before MI and there was a significant decrease in edema, hemorrhage, and mononuclear cells in the heart tissue at 24 h post-MI and fibrosis on day 7 post-MI. Conclusion: HN administration before MI has a cardioprotective effect on rats via the Notch signaling pathway.
Keywords: Myocardial infarction; humanin; Notch1; Hes1; Dll4